Immigrants in the Nation's imaginary. An outlook from the organizations of three Latin American communities in XXI Century Argentina (Colección, 2017)
This article examines how Latin American immigrants in Argentina –especially Bolivians, Paraguayans and Chileans- identify themselves in terms of national identity and to what extent those identifications impact on their possibilities of social and political participation through their communities in the destination country. It will explore then the role that Latin American migrants’ organizations are playing in the struggle for the recognition of their rights and its place within the Argentine national imaginary. Firstly, it will describe the emergence of social networks among Paraguayan, Bolivian and Chilean immigrants, focusing on their institutions and comparing both leadership profiles and types of community-based organizations. Secondly, it will examine the ways in which national identities -linked not only to the place of origin but also of destination- are being created. Through the analysis of the discourses of some of their communitarian leaders, the aim will be to draw some conclusions about the dynamics of acceptance and rejection towards Latin American migrants in Argentina: Are they being perceived –or perceive themselves- as “included” into the national project and identity? To what extent the idea of Argentina as a “nation of immigration” is something more than a myth? The study of civil reactions to the migratory phenomenon –especially of communitarian organizations- will allow an understanding of how regional migrations have been impacting on argentine’s national society and of how Latin American immigrants are struggling for their rights in the twenty-first century.
Keywords: Immigration; Identity; Imaginary; Nation; Exclusion / Inclusion